Smart City Policy: Strategy and Implementation to Realize Smart Urban Governance in Indonesia - Sulistyaningsih, Tri; Purnama, Rika Ayu; Kulsum, Umi (Journal of Governance and Public Policy, 2023)
This paper delves into the intricate landscape of Smart City policies, strategies, and implementation challenges in Indonesia, with a particular emphasis on smart urban governance. Despite significant global discourse, the formulation and execution of Smart City initiatives in Indonesia remain fragmented, resulting in inconsistencies across governance frameworks. To address these gaps, this study systematically analyzes 213 Scopus-indexed articles on "smart city policies" and "smart urban governance" using VOSviewer and Nvivo 12 Plus, alongside an in-depth examination of relevant regulatory documents. The findings underscore three pivotal strategies for advancing smart urban governance in Indonesia: (1) the imperative for cohesive, national-level support in shaping Smart City policies, (2) the strategic incorporation of technological advancements to drive effective implementation, and (3) the critical need to overcome institutional and human resource constraints that hinder progress. Moreover, the study highlights key urban challenges, such as mega-urbanization, urban management, affordable housing for low-income populations, sustainable infrastructure development, and disaster resilience, as pressing concerns. The state of the art in this research lies in its innovative use of advanced analytical tools VOSviewer and Nvivo to map and assess policy and governance frameworks, a methodological approach seldom applied in this context. The novelty of the study resides in its proposal of a multi-level governance model that harmonizes national policy directives with the distinct needs of local urban governance, integrating technological, institutional, and regulatory dimensions for a more cohesive and sustainable Smart City strategy. This study contributes by mapping the challenges and opportunities of Smart City policy in Indonesia and proposing a multi-level approach to align national policy with local governance needs.